DAMPAK PLATFORMISASI PADA TATA KELOLA MUSIK STREAMING DI INDONESIA DAN PERLAWANANNYA OLEH MUSISI INDIE LOKAL - Resmadi, Idhar (Fakultas Seni Rupa dan Desain ITB, 2024)
Issues of inequality and injustice have become prevalent in economic-political discourse in digital media, particularly because of the impact of platformization on digital streaming platforms. This article examines how platformization shapes cultural production, the governance of the music streaming industry, and the resistance againts its dominance in Indonesia emerge. Through observations and interviews with indie music practitioners in Indonesia, this article discusses platform-based cultural production and the rise of new power held by aggregators in the music-streaming industry. The discussion is divided into the impact of platformization on indie musicians and alternative production patterns that challenge platform-based cultural production in Indonesia. This article aims to provide an overview of the impact of platformization on indie musicians in Indonesia and to explore alternative methods that encourage musicians to gain independence from platforms.